Women’s National Volleyball - Basketball teams in Albania performed in Drop Jump 60 cm - Lleshi, Enkeleida; Msc. Denis Nuriu, (European Journal of Multidisciplinary Studies, 2020)
Volleyball and Basketball women’s have different performances from each other due to their special specifics of the game. From the specificity of their training, there are differences in the physical qualities of individual and team sports performance, where one of the elements is vertical jumping. This study is concentrated on two teams: Women’s Volleyball Team (V) and Women’s Basketball Team (B) 15 members each, focusing on 30 subjects. Players were measured in physical parameters; Age (V-24: B-27), Body Height (V-180.4cm; B-173.4cm), Body Weight (V-70.37kg; B-63.88kg), BMI (V-21.67 percent; B-20.93 percent). The players performed the test DJ60cm in the platform Leonardo Ground Force Reaction Plate (GRFP) which expresses Force max (kN), Power max (w/kg), Time Contact (TCs), Air Time (TAs), TA/TCs. The results obtained by GRFP showed different team values of the two sports in the parameters of Fmax V65.19-B74.07n/kg, Pmax V31.26-B23.06w/kg, TCs V0.231-B0.198, TAs V0.436-B0.34 and TA/TC?ec V1.96?-B1.71?ec. Results revealed that V players jumped higher (p, 0.001) than B players. Finally, the Drop Jump60cm test has different performance between individual players, despite the fact that in the team average it turned out that Volleyball players is higher in this test. Drop Jump is the typical plyometric test. Furthermore, tests such as DJ can be a useful method for assessing differences and monitoring vertical jump training programs from collective sports.
Keywords: drop jump, volleyball, basketball, players, air time.